A mora no direito tributario - Lins, Robson Maia (2008)
The aim of the present doctoral dissertation, presented to the Examining Board of the Post-graduate Program in Tax Law, was to analyze the tax juridical concept referred to as mora (delinquency). In order to achieve this objective using a scientific approach to the Law, we explored the levying procedures established by the tax norm known as Regra-matriz tax levy (by Brazilian Professor Paulo de Bastos) in conjunction with other norms of the tax system, comprising the normative calculation together with the Regra Matriz Tax Levy (Regra Matriz de Incidência Tributária RMIT). The reader will also note constant cross references to other juridical norms, beyond the scope of tax levy. There are many inclusions in fields governed by these norms which establish tax ancillary obligations and penalties that distort the Regra-Matriz tax levy model, as is the case concerning tax exemptions. Accordingly, there are normative calculations that do not always follow a chronological order in terms of the rise, suspension and extinction of the tax liability. This is indeed the case! The subject is broad and dynamic and often strays from the levy sequence deemed normal according to the precepts of the Brazilian Tax Code. Therefore, the subject matter of our study not only comprised the Regra-matriz of tax levy but all the norms that directly or indirectly consider the inertia of the creditor or the debtor as a fact support, whether in strictus sensus tax liability or in liability to rebate tax indebitum. We investigated the course of the rise and extinction of tax liability, including the liability suspension of tax credit; from the rise to the extinction of repetition, offset or rebate of tax indebitum, while analyzing the structure, function and objective of the mora (delinquency). We addressed the events of tax credit liability suspension as well as the provisional remedies of abstract control (controle abstrato) of the Constitution in order to study the possible configuration of the delinquent juridical facts, pre-requisites for the levying of sanctioning norms. The expressions multa de mora (delinquency fine), multa de ofício (fine determined by judge), multa penal (criminal penalty), multa sancionatória (penalty sanction), as well as delinquent interest shall be analyzed at a syntactic, semantic and pragmatic level while seeking to explain synonymous expressions within the context of tax legislation, and identical expressions with different content and function. We have employed the analytical method for structural areas, and the hermeneutic approach for semantic and pragmatic fields, such that this study adopted the doctrine line referred to as legal constructivism, or more precisely logic and semantic-structured constructivism